Some Generalized Lacunary statistically difference double semi-normed sequence spaces defined by Orlicz function - doi: 10.4025/actascitechnol.v35i1.15523 - Esi, Ayhan; Hazarika, Bipan (Acta Scientiarum. Technology, 2012)
In this article, we have introduced the idea of statistically convergent generalized difference lacunary double sequence spaces [Â¯w2 (M, Î”n, p,q)]Î¸, [Â¯w2 (M, Î”n, p,q)]Î¸ and defined over a semi norm space (X, q). Also we have study some basic properties and obtained some inclusion relations between them. Â